1995
DOI: 10.2500/105065895781873881
|View full text |Cite
|
Sign up to set email alerts
|

Chemosurgery with Trichloroacetic Acid for Allergic Rhinitis

Abstract: The use of 80 w/v% solution of trichloroacetic acid (TCA) for the treatment of allergic rhinitis was reported. The solution was applied to the inferior turbinates only once bilaterally. The result of the treatment in 77 nonselected cases of perennial allergic rhinitis for over 3 years showed that an improvement was obtained in 72% for nasal obstruction, 60% for sneezing, and 50%for watery nasal discharge. The result o.fprovocation tests after treatment showed an improvement in 77% of the cases, and the hista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…. As we reported elsewhere, 13 I n the present study, it was observed that the inferior turbinate in the treated side showed a significant decrease in the number of infiltration MC T , which is directly associated with the development of allergic symptoms that would indicate that our method of chemosurgery was effective against the symptoms of allergic rhinitis. In contrast, the decrease in the number of MC TC that was reported to be related to tissue restoration after the allergic reaction 11.…”
Section: Or Jsupporting
confidence: 66%
“…. As we reported elsewhere, 13 I n the present study, it was observed that the inferior turbinate in the treated side showed a significant decrease in the number of infiltration MC T , which is directly associated with the development of allergic symptoms that would indicate that our method of chemosurgery was effective against the symptoms of allergic rhinitis. In contrast, the decrease in the number of MC TC that was reported to be related to tissue restoration after the allergic reaction 11.…”
Section: Or Jsupporting
confidence: 66%
“…1 Various methods of turbinate surgery have been established with good outcomes for nasal congestion. [1][2][3][4][5][6][7][8][9][10][11][12]18,19 However, the selection of the surgical tech-niques appears to be based more on the surgeon's preference than on a critical assessment of the outcomes for the treatment. 8 In addition, there have been few reports describing the long-term effects of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Turbinate surgery is a useful treatment for perennial allergic rhinitis. 1 Various methods of turbinate surgery, including laser treatment (CO 2 , 2–4 Ho:YAG, 5 potassium‐titanyl phosphate 6 ), chemical treatment (trichloroacetic acid 7 ), and the submucosal technique, 1,8 have been established with good outcomes for allergic rhinitis. Because surgery is more invasive than other types of treatments, such as medication or immunotherapy, it is important that the surgery results in sustained improvement in the patient's quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques were employed in the last few decades in order to determine a volumetric reduction of the inferior turbinates as well as in the treatment of recurrent epistaxis from submucosal decongestion to partial or total removal of the turbinates, from cauterization to cryosurgery, from mono-or bipolar electrocoagulation to surgery with the Nd:YAG, CO 2 or KTP laser [2][3][4][5][6][7][18][19][20][21][22][23][24][25][26][27]. The use of APC in rhinosurgery has allowed a greater control of the thermocoagulation phenomenon restricting it to the most superficial areas of the tissue; the argon plasma action combines short-time operation and considerable tolerability with the absolute absence of hemorrhagic complications and of nasal packing.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 laser [1,2], YAG laser [2,3], conventional electrocautery [4], cryotherapy [5,6], chemosurgery [7] and turbinectomy or submucosal turbinectomy [4,6] Recently, a new electrosurgical modality, argon plasma coagulation (APC), which has been used successfully on gastrointestinal lesions under endoscopy, has been introduced into the otolaryngological field. Its application permits a rapid and little obstructive hemostasis of wide hemorrhagic areas.…”
Section: Introductionmentioning
confidence: 99%